The value of using multi-methods in law courses in higher education - Acquah, Daniel Opoku; Acquah, Ama Opoku; Acquah, Emmanuel Opoku (Taylor & Francis, 2025)
This article examines the added value of using multi-methods in an intermediate law course for final-year undergraduate and master’s degree students at a medium-sized university in South West Finland. The study involved 23 law students from various countries who were about to complete their bachelor’s studies or pursue their master’s degrees. The content analysis and constant comparative approach results indicated that employing multiple teaching methods in the course significantly enhanced the students’ learning. The treaty simulation, based on the ongoing negotiations at two international organisations – the World Intellectual Property Organization (WIPO) and the World Trade Organization (WTO) – had the most significant impact on the students. Participants felt accountable for their learning, gained self-confidence, developed a sense of fulfilment, and learned about the complexities of negotiating international treaties and building consensus. They felt more prepared for similar roles in their future careers. The course highlights the benefits of active learning and the role of simulations in developing professional competence and communication skills. It suggests that faculty should incorporate multi-methods and simulations, when possible, to teach law.